1999
DOI: 10.1007/s004300050093
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of poliovirus type 1 infection by iron-, manganese- and zinc-saturated lactoferrin

Abstract: In this study we investigated the inhibitory activity of different milk proteins on poliovirus infection in Vero cells. Proteins analyzed were mucin, alpha-lactalbumin, beta-lactoglobulin, and bovine and human lactoferrin. Viral cytopathic effect was not prevented by mucin, alpha-lactalbumin or beta-lactoglobulin, whereas the lactoferrins tested were able to inhibit the replication of poliovirus in a dose-dependent manner. Further experiments were carried out in which apo- and native lactoferrin or lactoferrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(82 citation statements)
references
References 28 publications
4
77
0
1
Order By: Relevance
“…Alternatively, direct binding of lactoferrin to both the cell surface and virus particles cannot be excluded. This is consistent with reports by Marchetti et al (1999), who observed that lactoferrin bound to the surface of Vero cells, the host they used for PV. Marchetti et al (1996) have shown that while lactoferrin bound to the heparin sulphate surface receptors, the primary cell surface receptors required by the HSV type 1 (HSV-1), it also bound to the HSV-1 particles.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Alternatively, direct binding of lactoferrin to both the cell surface and virus particles cannot be excluded. This is consistent with reports by Marchetti et al (1999), who observed that lactoferrin bound to the surface of Vero cells, the host they used for PV. Marchetti et al (1996) have shown that while lactoferrin bound to the heparin sulphate surface receptors, the primary cell surface receptors required by the HSV type 1 (HSV-1), it also bound to the HSV-1 particles.…”
Section: Discussionsupporting
confidence: 93%
“…The method described by Marchetti et al (1999) was adapted to determine the interaction of bovine lactoferrin with the CRFK and MEK cells. Cells were grown on sterile glass cover-slips until semi-confluent and were incubated in tissue culture medium alone or together with either bovine lactoferrin or BSA (1 mg ml )1 ) for 1 h at 37°C in an atmosphere containing 5% CO 2 and 100% relative humidity.…”
Section: Assessment Of Effects Of Lactoferrin and Lactoferricin B Agamentioning
confidence: 99%
“…There was no evidence that lactoferrin, which binds to the LDL receptor [17], could inhibit the growth of rhinovirus 2 or the two clinical rhinovirus isolates. Lactoferrin inhibits poliovirus absorption to cells and, in combination with zinc, can actually inhibit poliovirus (a similar virus to rhinoviruses) replication [17]. The present study found that only rhinovirus-speci®c sIgA neutralisation inhibited the binding of rhinoviruses.…”
Section: Resultsmentioning
confidence: 99%
“…However, lactoferrin of bovine origin can inhibit growth of simian rotavirus SA11 [16], as can ganglioside GM1 [4]. Either bovine or human milk lactoferrin can interfere with growth of poliovirus type 1 [17]. Vitamin A (a lipid-containing compound) inhibited growth of simian virus 40 [18].…”
Section: Introductionmentioning
confidence: 99%
“…Not only does it inhibit the growth of many bacteria, it can even kill them (Kalmar and Arnold, 1988;Miehlke et al, 1996;Groenink, 1999). It also can inhibit the infection of some organisms by some viruses (Chen et al, 1987;Hasegawa et al, 1994;Marchetti et al, 1999). It has been used in gene transfer to produce virus-resistant transgenic tobacco (Zhang et al, 1998a,b).…”
Section: Introductionmentioning
confidence: 99%